A Student-Driven Guide for Project-based Learning - (:unkn) unknown (My University, 2020)
This action research study proposes the need for and examines the usefulness of a Student-Driven Guide for Project-Based Learning. The Guide was designed to give students guidance and structure in carrying out and documenting a project as a part of a class, or when students are working independently from a teacher. The Guide was informed by the educational theories of Constructionism, Student-Driven Learning, and Cross-Disciplinary Learning. It was tested with a group of high school students who used the Guide to create a series of multimedia photography projects. Completed Guides and student surveys about the experience were then collected and analyzed to determine if the Guide was useful to students and how it might be improved to better support student performance in the future. The findings of the study include data on positive and negative student engagement with the PBL Guide, areas of the Guide that need to be reviewed, student struggles with conceptual writing, and overconfidence in final student outcomes. The study concludes that the PBL Guide is helpful to students in an organizational capacity but needs further iterative changes to improve its effectiveness. These changes are addressed using action research methods in the form of a revised mockup for a digital PBL Guide that other researchers have the opportunity to build on in the future.
Keywords: Documentation; Educational Tool; Guide; Project-Based Learning; Student-Centered; Student-Driven